Педагогика – теория и практика социального управления - Орлов, Е.В. (My University, 2013)
This article deals with the concept of social control. Highlights key features and modes of governance. Rationale understanding the pedagogy as a branch of social management.The conditions under which education can be considered a social science.Considered the concept of sredovogo approach as a basis for social management technology